Business Performance Determinant and The Role of Financial Performance as Mediating Variabel - Septianingsih, Laela; Pratama, Bima Cinintya; Wahyuni, Sri; Mudjiyanti, Rina (E-Jurnal Akuntansi; Vol 35 No 4 (2025)DO - 10.24843/EJA.2025.v35.i04.p10, 2025)
The rapid development of MSMEs has led to high competition for Micro, Small, and Medium Enterprises in Banyumas Regency. This study was conducted to examine the implementation of MSME performance in MSME actors in Banyumas Regency by considering the influence of financial literacy, financial attitudes, financial performance, competition intensity, and government support. This research uses quantitative methods, the sampling technique is stratified, and the number of samples is 198 respondents. This research uses the Smart-PLS analysis method. The results of the analysis show that financial literacy, financial attitudes, financial performance, competition intensity, and government support have a positive and significant effect on MSME performance. The implication resulting from this research is that MSME actors must optimize their business management by improving business performance in these MSMEs. Keywords: Financial Literacy; Financial Performance; Competitive Intensity; Government Support; Business Performance